Dispute Settlement Mediation Marriage Problems and Solutions - Elly Lestari (IHSA Institute, 2021)
Mediation in Indonesia is regulated based on PERMA No. 1 of 2016 concerning Mediation Procedures in Courts. One of these regulations is used for mediation to resolve marital disputes. Mediation is a process of dispute resolution through the process of negotiation or consensus between the parties, assisted by a mediator who does not have the authority to decide or force a settlement. Should there be mediation at the Religious Court, dispute resolution is more towards reuniting the two conflicting parties. However, in the process of mediation in divorce cases, it was found that half of the mediation was carried out in divorce cases, and from the mediation that was carried out only a small proportion managed to make peace. So it can be said that the mediation process is still ineffective. There are many aspects that can affect the success of mediation, so there is a need for better evaluation and solutions from the relevant agencies in an effort to increase the success of mediation from the implementation of mediation, which in the end can reduce divorce cases.